Living the Qur'an in the Numpang Sedekah Tradition: Almsgiving Practice in the Muara Karang Village Community, Empat Lawang Regency - Agustini; Yuhaswita; Refileli; Jonsi Hunadar; Sultan Gholand Astapala; Dewi Aprilia Ningrum (Mimbar Agama Budaya, 2026)
This research diverges from the phenomenon that occurs in the community of Muara Karang Village, which is undoubtedly influenced by the religious beliefs they hold. These beliefs are derived from the Qur'an and the Hadith of the Prophet, which form the interaction of society with the Qur'an. The text of the Qur'an is used as a practice in the execution of traditions. The purpose of this investigation is to portray the tradition of the Lintang community of Muara Karang Village, Pendopo District, Empat Lawang Regency, which utilizes the Qur'an as its foundation for the traditional procession of "Numpang Sedekah" in the Lintang Community of Muara Karang Village, Empat Lawang Regency. This investigation is a field study that employs a phenomenological approach and a living Al-Qur'an. The data were collected through direct observation (participatory observation), literature studies, and documentation. Qualitative analysis techniques were employed to analyze the data, both inductively and deductively. The findings of this investigation indicate that the "Numpang Sedekah" tradition in the Muara Karang Village Community is a reception of the first and second verses of Surah al-Kautsar in the Qur'an. This tradition was established in the community as a gesture of gratitude for the favors that have been bestowed, including sustenance and success in achieving desired objectives. As a result, the local community conducts a thanksgiving or almsgiving ceremony at the family home.